A novel peptide conformation: the γ-bend ribbon. Issue 42 (15th October 2018) - Drouillat, Bruno; Peggion, Cristina; Biondi, Barbara; Wright, Karen; Couty, François; Crisma, Marco; Formaggio, Fernando; Toniolo, Claudio
Abstract : Conformational analysis of oligopeptides based on the repeating –( S )-(αMe)Aze-( S )-Ala– dyad allowed the characterization of a 3D-structure featuring multiple, non-consecutive γ-bends. Abstract : Unlike the extensively investigated relationship between the peptide β-bend ribbon and its prototypical 310 -helix conformation, the corresponding relationship between the narrower γ-bend ribbon and its regular γ-helix counterpart still remains to be studied, as the latter 3D-structures have not yet been experimentally authenticated. In this paper, we describe the results of the first characterization, both in the crystal state and in solution, of the γ-bend ribbon conformation using X-ray diffraction and FT-IR absorption, electronic CD and 2D-NMR spectroscopies applied to an appropriate set of synthetic, homo-chiral, sequential dipeptide oligomers based on ( S )-Ala and the known γ-bend inducer, C α -tetrasubstituted, N -alkylated α-amino acid residue ( S )- C α -methyl-azetidine-carboxylic acid.